1996
DOI: 10.1177/009365096023002001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing News Media Influences on the Formation of Whites' Racial Policy Preferences

Abstract: Researchers have shown that news discourse contains images, episodes, themes, and vocabulary that comprise a negative portrayal of Blacks. But evidence linking news media content to Whites' racial policy opinions has lacked clear specification of the opinion formation process and mechanisms of news media influences on such process. This study mimics Whites' reasoning process via a causal model involving ideological orientations, affect toward Blacks, assessment of situations of racial inequality, and causal at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Other studies (e.g., Gilens, 1996;Pan & Kosicki, 1996) have analyzed how perceptions of racial minority groups (e.g., African Americans) by majority (White) Americans affected majority opinions on race related issues. Similarly, we are interested in stereotypes of a racial minority by the majority, assuming that in general, majority opinions are more likely to affect public policy than minority opinions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies (e.g., Gilens, 1996;Pan & Kosicki, 1996) have analyzed how perceptions of racial minority groups (e.g., African Americans) by majority (White) Americans affected majority opinions on race related issues. Similarly, we are interested in stereotypes of a racial minority by the majority, assuming that in general, majority opinions are more likely to affect public policy than minority opinions.…”
Section: Methodsmentioning
confidence: 99%
“…Building on the work of , Pan and Kosicki (1996) analyzed how the news media might influence the reasoning chain of White Americans regarding racial policy. They predicted that use of information media will strengthen the effect of ideology on opinions regarding racial issues, while "non-information" television use will strengthen the influence of race affect on opinions.…”
Section: News Media and Racial Policy Reasoningmentioning
confidence: 99%
“…Research shows that media can affect specific viewer policy beliefs and attitudes (Pan & Kosicki, 1996;Tan, Fujioka, & Tan, 2000). Pan and Kosicki (1996) found that conservatism was a much stronger negative predictor of support for racial equality policy among those who scored high on information-oriented media use. Overall, media can impact viewer policy beliefs, and this influence may be through framing mechanisms.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Of additional interest to the model of policy reasoning formulated by Tan et al (2000) is whether and how these responses later translate into viewers' political decisions. Research on media use and racial policy positions informs this outcome, demonstrating a link between responses to media content and subsequent policy reasoning (Gilliam, 1999;Mendelberg, 1997;Pan & Kosicki, 1996;Valentino, 1999).…”
Section: Support For a Media-based Model Of Policy Reasoningmentioning
confidence: 99%
“…Finally, with a survey design, Pan and Kosicki (1996) investigated the influence of news consumption on race-based policy decisions. Specifically, they assessed the extent to which news exposure affected the relevance and weight of factors taken into consideration when making race-based policy determinations.…”
Section: Support For a Media-based Model Of Policy Reasoningmentioning
confidence: 99%